Retail Internationalization: Agenda for future Research Directions - Ayşegül Seferoğlu (Journal of International Trade, Logistics and Law, 2024)
In the midst of growing tendencies towards protectionist trade practices as we approach the end of the first quarter of the 21st century, the retail internationalization practice has become uncertain more than ever. Yet the need for retail internationalization is still prerequisite, not an option. The purpose this paper is to put forward a series of propositions, a research agenda, which might be found useful by the academicians for their future research on retail internationalization that will help the practitioners to navigate in these times of uncertainties.